A JURIDICAL ANALYSIS OF THE CRIMINAL LIABILITY OF PERPETRATORS OF ONLINE CHILD SEXUAL EXPLOITATION - Charenitha, Aurellia; Firmansyah, Hery (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study analyzes the criminal liability of perpetrators of child sexual exploitation conducted through online media under Indonesian criminal law. The research applies a normative juridical method with statutory and case approaches. The findings reveal that perpetrators can be held criminally liable if proven to have committed the offense with culpability, as stipulated in the Indonesian Criminal Code, the Child Protection Law, the Electronic Information and Transactions Law, and the Pornography Law. Although the existing legal framework is relatively adequate, law enforcement remains hampered by difficulties in digital evidence collection, overlapping regulations, and low levels of public digital literacy. The study highlights the need for legal reform and preventive strategies focusing on digital literacy and child protection to strengthen the national legal system and ensure comprehensive protection for children in cyberspace in accordance with the best interest of the child principle.